======================================================
Explanation:
Plug in x = 1
f(x) = 17-x^2
f(1) = 17-1^2
f(1) = 17-1
f(1) = 16
Repeat for x = 5 to find that f(5) = -8
Now we'll use the formula below to find the average rate of change from x = a to x = b.
[tex]m = \frac{f(b)-f(a)}{b-a}\\\\m = \frac{f(5)-f(1)}{5-1}\\\\m = \frac{-8-16}{4}\\\\m = \frac{-24}{4}\\\\m = -6\\\\[/tex]
The average rate of change is -6
The formula is basically the slope formula, more or less. So that's why I used 'm' to represent the average rate of change.
The average rate of change on the interval [1,5] is the same as finding the slope through the lines (1, 16) and (5, -8)